In situ growing 3D-Cu coating to improve the reversibility and reaction kinetics of Zn metal anodes - Liang, Lianbao; Hang, Lifeng; Xie, Shuangcong; Men, Dandan; Jiang, Guihua; Chen, Yiyu (Frontiers in Chemistry, 2022)
Zinc metal anode is the most promising metal anode materials in aqueous battery systems due to its low cost and high theoretical capacity. However, it still suffers from irreversible reactions as premature failure of the dendrites/dead Zn during Zn stripping/plating, resulting in inferior cycling stability of the Zn-based full cell. Here we demonstrate a facile 3D-Cu alloy-coating to improve Zn reversibility by providing spatial voids to accommodate the plated Zn to form dendrite-free morphology. Combining the larger 3D surface and the alloying-dealloying process, the Zn anode reactions exhibits enhanced reaction kinetics to meet the large operating current densities. The 3D-Cu coated Zn anode can deliver improved cycling stability for 350 hours under large areal capacity of 3 mAh cm‒2. It also enables the MnO2-Zn at full cell level to achieve the specific capacity of 205 mAh g-1 and longer cycling for 350 cycles with 87.4 % retention of the initial capacity. This research provides a new pathway to achieve high reversible Zn metal chemistry.